Multidimensional Analyses of Motivations for Pig Farming by the Residents of Kupang, Nusa Tenggara Timur, Indonesia - Sabat, Diana Meliani; Haryadi, Fransiskus Trisakti; Ngadiyono, Nono (Jurnal Veteriner; Vol 25 No 1 (2024), 2024)
The most popular business for the people of Kupang City is the pig farming business. In doing their business, farmers certainly have certain motivations. So far, motivation is often seen as one complete variable, even though in doing business farmers do not only look at one reason, but see multidimensionally from various dimensions. The dimensions in question are economic, socio-cultural and household food waste utilization motives. This study was aimed to evaluate and analyze the multidimensionality of priority motivations in pig farming and determine which motives are most prioritized by farmers in conducting a pig business in Kupang City. There were 20 pig farmers involved in this study selected using purposive sampling method located in three sub-districts in Kupang City. The variables measured were farmers’ motivations (economic motive, socio-cultural motive, and food waste utilization motive, farmer time and labor). Data analysis was conducted using the Analytic Hierarchy Process (AHP). The results showed that socio-cultural motives had the highest priority value (0.4032), followed by economic motives (0.3162) and household food utilization motives (0.2806).